2020
DOI: 10.1007/s00780-020-00439-y
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency trading with fractional Brownian motion

Abstract: In the high-frequency limit, conditionally expected increments of fractional Brownian motion converge to a white noise, shedding their dependence on the path history and the forecasting horizon and making dynamic optimisation problems tractable. We find an explicit formula for locally mean–variance optimal strategies and their performance for an asset price that follows fractional Brownian motion. Without trading costs, risk-adjusted profits are linear in the trading horizon and rise asymmetrically as the Hurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Overall, this article sheds new lights on the informational content of fractional models. It confirms in a new manner previous results on the forecast of fBm in finance [39,38,32]. It also deepens the understanding of the stationary inverse Lamperti transform of the fBm [29].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, this article sheds new lights on the informational content of fractional models. It confirms in a new manner previous results on the forecast of fBm in finance [39,38,32]. It also deepens the understanding of the stationary inverse Lamperti transform of the fBm [29].…”
Section: Introductionsupporting
confidence: 88%
“…for all s, t ∈ R. In finance, the propensity of the fBm to be forecast contradicts the EMH and is at the root of many statistical arbitrage strategies [39,38,32]. It is thus relevant to quantify the market information of such a dynamic.…”
Section: Log-prices Following An Fbmmentioning
confidence: 99%
“…A possible direction of future research is to extend model (1) with fractional Brownian motion. Recently, the fractional Brownian motion has fruitful applications in finance such as financial modelling, option pricing, optimal portfolio selection and high frequency trading, see Guasoni et al [13], Guasoni et al [14], Kříž and Szała [15] and Rostek and Schöbel [16] for more details. Another interesting issue of future research is to explore other real problems in finance market based on model (1) and test the efficiency of model (1) via analyzing the real financial data.…”
Section: Discussionmentioning
confidence: 99%
“…With a relevant geometric formalism the authors show that the Bellman function is the unique viscosity solution of the corresponding HJB equation. On the other hand, in the high-frequency limit, the paper [6] finds an explicit formula for locally mean-variance optimal strategies. In the limit, it is shown that conditionally expected increments of fractional Brownian motion converge to a white noise, shedding their dependence on the path history and the forecasting horizon and making dynamic optimisation problems tractable.…”
Section: Introductionmentioning
confidence: 99%